Pengaruh Kompetensi Terhadap Kinerja Karyawan Pada PT. PLN Indonesia Power UBP Mahakam - Nurul Izzah; Sofia Ulfa Eka Hadiyanti; Askiah Askiah (Pelantar Press, 2025)
This study aims to analyze the effect of competence on employee performance at PT PLN Indonesia Power UBP Mahakam. Competence in this research comprises five dimensions: knowledge, skills, selfconcept, personal characteristics, and motives. The study employs a quantitative approach with a survey method, involving the entire population of 50 employees using a total sampling technique. Data were collected through questionnaires and analyzed using simple linear regression. The results show that competence has a positive and significant effect on employee performance. Among the dimensions, knowledge and skills are the most dominant factors in improving work quality, task execution, and responsibility. These findings underscore the importance of competence development as a key strategy to enhance performance and competitiveness, particularly in the dynamic energy sector. Therefore, management at PT PLN Indonesia Power UBP Mahakam is advised to continuously develop training and competence development programs to support the achievement of the company’s strategic goals